Early development of decreased β‐cell insulin secretion in children and adolescents with hemoglobin H disease and its relationship with levels of anemia. Issue 4 (25th December 2019) - Nakavachara, Pairunyar; Kajchamaporn, Worarat; Pooliam, Julaporn; Viprakasit, Vip
Abstract: Background: Diabetes mellitus (DM) associated with iron overload has been reported among adults with transfusion‐dependent thalassemia and those with non‐transfusion‐dependent thalassemia (NTDT), especially in β‐thalassemia disease. However, little is known about glucose metabolism and how early its dysregulation can develop in α‐thalassemia hemoglobin H (Hb H) disease, which is one of the most common types of NTDT worldwide. Procedure: We prospectively calculated glucose metabolism index in 40 patients (aged 10–25 years) with Hb H disease. Glucose metabolism data were compared between patients with deletional versus nondeletional Hb H, and between patients with normal versus abnormal insulin secretion/sensitivity. Results: Despite normal glucose tolerance in all patients, 52.5% had abnormal insulinogenic index indicating decreased β‐cell insulin secretion. Patients with functional hemoglobin < 8 g/dL had significantly higher percentages of abnormal insulinogenic index. There was no significant difference in abnormal insulinogenic index between deletional and nondeletional Hb H. Conclusion: Decreased β‐cell insulin secretion is highly prevalent among children and adolescents with Hb H disease, and it is associated with levels of functional anemia at baseline, but not with the type of Hb H disease. This result warrants heightened awareness among hematologists due to potentially increased risk of DM later in life.